Klasifikasi Jenis Buah dan Sayuran Menggunakan SVM Dengan Fitur Saliency-HOG dan Color Moments - Yohannes Yohannes; Muhammad Rizky Pribadi; Leo Chandra (ELKHA : Jurnal Teknik Elektro, 2020)
Fruit is part of a plant that comes from the flower or pistil of the plant and usually has seeds. Meanwhile, vegetables are leaves, legumes, or seeds that can be cooked. Fruits and vegetables have many variants that can be distinguished based on color, shape, and texture. The Saliency-HOG feature and Color moments were used in this study to extract shapes and colors features in fruit and vegetable images. In this study, the Support Vector Machine (SVM) method was used to classify the types of fruit and vegetables. The dataset used in this study is a public dataset consisting of 114 images of fruit and vegetables. Each type of fruit and vegetable contains 100 images consisting of 70 images as training data and 30 images as testing data. There are 4 saliency features used in the testing phase, namely Region Contrast (RC), Frequency-tuned (FT), Histogram Contrast (HC), and Spectral Residual (SR). Based on the test results, the Saliency-HOG and Color Moments features were able to provide good results with the best precision, recall, and accuracy being 98.57%, 98.55%, and 99.120%, respectively.